2022
DOI: 10.3390/ijms23063260
|View full text |Cite
|
Sign up to set email alerts
|

NPFF Decreases Activity of Human Arcuate NPY Neurons: A Study in Embryonic-Stem-Cell-Derived Model

Abstract: Restoring the control of food intake is the key to obesity management and prevention. The arcuate nucleus (ARC) of the hypothalamus is extensively being studied as a potential anti-obesity target. Animal studies showed that neuropeptide FF (NPFF) reduces food intake by its action in neuropeptide Y (NPY) neurons of the hypothalamic ARC, but the detailed mode of action observed in human neurons is missing, due to the lack of a human-neuron-based model for pharmacology testing. Here, we validated and utilized a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…NPFFR2 positivity was abundant in both NPY (64%) and POMC (40%) cells, but NPFFR2-expressing cells were also detected in the somatostatin-(28%), dopamine-(26%), nociception-(16%), and NPFFR1-(16%) producing neuronal populations [173,174]. Human dual ISH data demonstrated that, similarly to mice, NPFFR2 mRNA was predominantly expressed in NPY-and GABA-producing neurons of the ARC, whereas in contrast to mice, POMC neurons did not show any NPFFR2 signal [175]. These data suggest that NPFFRs are central mediators of several aspects of the regulation of homeostasis, including the stress response.…”
Section: The Chemical Nature Of Npffr-bearing Cellsmentioning
confidence: 97%
“…NPFFR2 positivity was abundant in both NPY (64%) and POMC (40%) cells, but NPFFR2-expressing cells were also detected in the somatostatin-(28%), dopamine-(26%), nociception-(16%), and NPFFR1-(16%) producing neuronal populations [173,174]. Human dual ISH data demonstrated that, similarly to mice, NPFFR2 mRNA was predominantly expressed in NPY-and GABA-producing neurons of the ARC, whereas in contrast to mice, POMC neurons did not show any NPFFR2 signal [175]. These data suggest that NPFFRs are central mediators of several aspects of the regulation of homeostasis, including the stress response.…”
Section: The Chemical Nature Of Npffr-bearing Cellsmentioning
confidence: 97%
“…However, it is known that neuronal pathways in the hypothalamus control food intake and are key regulators for both monogenic and polygenic obesity 5 . Several human stem cell-derived hypothalamic neuron models have been developed [7][8][9][10][11] and used to investigate the molecular basis of body weight regulation 7,[11][12][13][14][15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%